“Balako Bahuma” Tradisi Perladangan Suku Dayak Krio sebagai Upaya Arif-Bijaksana Memelihara Alam Semesta: Sebuah Elaborasi Filosofis-Fenomenologis-Kultural dalam Terang Ensiklik Laudato Si’ Artikel 144. - Agustinus Tamtama Putra (STP St. Bonaventura Medan, 2025)
Dayak Krio's indigenous culture vis a vis consumerist culture is quite disturbing and unsettling. This is in line with a trend specifically highlighted by Pope Francis in his encyclical Laudato Si'. In this paper I would like to elaborate on my own culture, the Dayak Krio culture, in its challenge to the consumeristic culture in the perspectives raised by the Holy Father in the encyclical. For the Holy Father, culture is the preserving agent of the universe. This role is aligned with the Dayak Krio cultural practice of balako bahuma. This congruence of role and action is being confronted by another factor that brings a consumeristic culture into people's lives. This factor is caused by giant capitalist projects. The study found that returning to nature and learning from local cultures is an ethical and practical imperative of modern man today given the catastrophic dangers of nature that are ready to threaten at any time as a result of human consumerist deforestation.